Menelusuri Kembali Peran Investasi Modal Manusia dan Modal Fisik Dalam Meningkatkan Pertumbuhan Produktivitas - Hendarmin, Hendarmin (Fakultas Ekonomi dan Bisnis, UNTAN, 2019)
The purpose of this study is to examine the impact of human capital on the level of economic productivity of regencies/cities in West Kalimantan Province. The data used in this study are panel data from 14 West Kalimantan Province/City Districts during the period 2012-2017 whose research results were analyzed using the Random Effect approach panel data regression analysis. The results of the study explained that the role of hum an capital as measured by the level of education, namely the average length of school (RLS), High School Participation Rate, and health level namely life expectancy (AHH) had a non-significant effect on economic productivity. Whereas physical capital investment (PMTB) has a significant influence on the level of economic productivity. The results of the analysis also show that for the human capital variable it has a smaller magnitude compared to the physical capital investment variable. Based on these results, it is concluded that the impact of human capital is very important in increasing economic productivity in the Regency/City of West Kalimantan Province.